59‐3: Ultra‐Precise Printing of Micrometer‐Size Interconnectors for High‐Resolution MicroLED Displays. Issue 1 (28th June 2021) - Wiatrowska, Aneta; Kowalczewski, Piotr; Fiączyk, Karolina; Witczak, Łukasz; Gadzalińska, Jolanta; Łysień, Mateusz; Schneider, Ludovic; Kosior, Łukasz; Granek, Filip
Abstract : We demonstrate a novel ultra‐precise deposition (UPD) technology for printing of micrometer size, mechanically robust, and high‐conductivity interconnectors in micro‐LED (µLED) displays. UPD allows maskless deposition of highly‐concentrated silver inks (even 85% wt. of metal content) on steps much higher than the width of the printed structure. The printed feature size is as small as 1 micrometer with the electrical conductivity up to 45% of bulk silver.